Enhanced intermolecular coulombic decay due to sulfur heteroatoms in thiophene dimer - Mootheril Thomas, Deepthy; Skitnevskaya, Anna D.; Ren, Xueguang; Dogan, Mevlut; Trofimov, Alexander B.; Kuleff, Alexander I.; Cederbaum, Lorenz S.; Pfeifer, Thomas; Dorn, Alexander (Communications chemistry, 2025)
Intermolecular Coulombic decay (ICD) is an important relaxation process of excited atoms and molecules in an environment, producing low-energy electrons that may contribute to radiation damage. Despite its significance, the mechanisms influencing ICD in molecular complexes remain unclear. Here, we investigate and unambiguously prove the ICD process in thiophene dimer, an aromatic ring with a third-row atom. Using multi-particle momentum coincidence spectroscopy, accompanied by high-level electronic structure calculations, we elucidate that the ICD process is initiated from the sulfur-containing inner-valence orbitals which are energetically below the Auger threshold. This leads to an enhancement in the emission of low-energy ICD electrons compared to other aromatic ring dimers. By utilizing this ‘ICD-only decay’ contribution we quantify ICD probabilities above the Auger threshold. This study reveals the pivotal role of sulfur in shaping the ICD electron spectrum, which can be implied to control the low-energy electron emission in biological systems.
Gesehen am 29.10.2025